The Strength of Restaurant Taxes in Garut Regency Through SWOT Analysis - Elsa Elpira; Lina Nurlaela; Muslim Al Kautsar (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
This study aims to determine the effectiveness and contribution of restaurant taxes in Garut Regency. The method used in this study is a qualitative method with a descriptive approach. Data collection methods are field studies, documentation, interviews and questionnaires. The method of data analysis used by the author is data reduction, presentation of data consultation drawing/verification. The analytical tool used is SWOT analysis. The results of this research show the effectiveness of the 2018-2021 restaurant tax in the "very effective" category. The 2018-2019 restaurant tax contribution was in the "less" category, but in 2020 it lowered the category to "very less," and in 2021, it returns to the "less" criteria.